Vaccination coverage among paediatric onco-haematological patients: an Italian cross-sectional study - Paola Giordano; Nicola Santoro; Pasquale Stefanizzi; Stefano Termite; Sara De Nitto; Francesco Paolo Bianchi; Paola Carmela Corallo; Giuseppe Lassandro; Silvio Tafuri (Taylor & Francis Group, 2021)
Children with onco-hematological diseases are at increased risk of infection. However, this risk can in part be controlled or reduced using currently available vaccines. Despite available evidence, in patients diagnosed with a hematological or oncological disease the vaccination schedule is often inappropriately discontinued. In this study we evaluated whether the diagnosis of an oncological or hematological disease is a determinant of noncompliance with recommended vaccinations. The study was carried out between March and April 2019. The population was composed of a convenience sample of 228 children cared for in the Pediatric Oncology Department and Pediatric Hematology Department of the Policlinico Giovanni XXIII Pediatric Hospital (Bari, Italy) from 2005 to 2015. Information on the immunization status of the patients was obtained from the Apulia regional immunization database (GIAVA). A post-diagnosis adherence score was calculated. The vaccination coverage was 87.7% for the DTaP-IPV-Hep B-Hib vaccine (3 doses), 68.7% for the pneumococcal vaccine (3 doses), 75.8% for the MMR vaccine (2 doses) and 75.1% for the varicella vaccine (2 doses). The average age at vaccination was older than that recommended by the National Vaccination Plan. A diagnosis of oncological disease and an older age at enrollment were risk factors for missing vaccinations. These results showed that the overall vaccination status of pediatric onco-hematological patients is suboptimal. Improving provider communication and establishing the hospital as the primary environment for vaccine administration may lead to better vaccination compliance in this group.